A note on the core topology - Kuczma, Marek (Annales Mathematicae Silesianae, 1991)
In the paper examples are given of some plane sets peculiar with respect to the core topology. Some simple topological properties of the cartesian product of sets lying in linear spaces endowed with the core topology are also proved.